RESPON PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max L. Merrill) AKIBAT INOKULASI CENDAWAN MIKORIZA ARBUSKULAR (CMA) DAN PEMUPUKAN FOSFAT ALAM - Nuraini, Lifta -; Lukiwati, Dwi Retno; Fuskhah, Eny (UNIVERSITAS LABUHANBATU, 2022)
Increased productivity of soybean (Glycine max L. Merrill) can be done through balanced and integrated fertilization. Rock phosphate and guano are natural sources of phosphor as an alternative to TSP fertilizer which has the advantage of not having a residual effect. The solubility of phosphor in natural phosphate is slow to be available. CMA inoculation can be done as an effort to increase the solubility of phosphor nutrients in natural phosphate. The aim of this study was to examine the response of soybean growth and yield due to CMA inoculation and natural phosphate fertilization, namely rock phosphate and guano. The research was conducted in January 2022 â€“ April 2022 at the Greenhouse of the Faculty of Animal Husbandry and Agriculture, Diponegoro University, Semarang. The study design used a monofactor completely randomized design (CRD) with the treatments being natural phosphate fertilization and CMA inoculation with 6 treatment levels (T1:TSP; T2:BP; T3:Guano; T4:TSP+CMA; T5:BP+CMA; T6:Guano+CMA). The treatment was repeated 8 times, so that 48 experimental units were obtained. The treatment was repeated 8 times, so that 48 experimental units were obtained. The research variables included plant height, number of trifoliate leaves, flowering age, dry weight of straw, number of filled pods, and dry weight of seeds. The data were analyzed by analysis of variance, then if it had a significant effect, it was continued with Duncan's multiple distance test (DMRT) at 5% level. The results showed that CMA inoculation treatment and natural phosphate fertilization could increase plant height, number of leaves, number of filled pods, and dry weight of seeds.Keyword: guano, mycorrhizal,Â phosphate, soybean